Diversity of fish sound types in the Pearl River Estuary, China - Wang,Zhi-Tao; Nowacek,Douglas P.; Akamatsu,Tomonari; Wang,Ke-Xiong; Liu,Jian-Chang; Duan,Guo-Qin; Cao,Han-Jiang; Wang,Ding (PeerJ, 2017)
Background Repetitive species-specific sound enables the identification of the presence and behavior of soniferous species by acoustic means. Passive acoustic monitoring has been widely applied to monitor the spatial and temporal occurrence and behavior of calling species. Methods Underwater biological sounds in the Pearl River Estuary, China, were collected using passive acoustic monitoring, with special attention paid to fish sounds. A total of 1,408 suspected fish calls comprising 18,942 pulses were qualitatively analyzed using a customized acoustic analysis routine. Results We identified a diversity of 66 types of fish sounds. In addition to single pulse, the sounds tended to have a pulse train structure. The pulses were characterized by an approximate 8 ms duration, with a peak frequency from 500 to 2,600 Hz and a majority of the energy below 4,000 Hz. The median inter-pulsepeak interval (IPPI) of most call types was 9 or 10 ms. Most call types with median IPPIs of 9 ms and 10 ms were observed at times that were exclusive from each other, suggesting that they might be produced by different species. According to the literature, the two section signal types of 1 + 1 and 1 + N10 might belong to big-snout croaker (Johnius macrorhynus), and 1 + N19 might be produced by Belanger’s croaker (J. belangerii). Discussion Categorization of the baseline ambient biological sound is an important first step in mapping the spatial and temporal patterns of soniferous fishes. The next step is the identification of the species producing each sound. The distribution pattern of soniferous fishes will be helpful for the protection and management of local fishery resources and in marine environmental impact assessment. Since the local vulnerable Indo-Pacific humpback dolphin (Sousa chinensis) mainly preys on soniferous fishes, the fine-scale distribution pattern of soniferous fishes can aid in the conservation of this species. Additionally, prey and predator relationships can be observed when a database of species-identified sounds is completed.
Keywords: Indo-pacific humpback dolphins; Hierarchical cluster analysis; Pearl River Estuary; Fish sound; Passive acoustic monitoring; Pulse train